A mismatch negativity study in Mandarin-speaking children with sensorineural hearing loss. (December 2016) - Fu, Mingfu; Wang, Liyan; Zhang, Mengchao; Yang, Ying; Sun, Xibin
Abstract: Objective: a) To examine the effects of sensorineural hearing loss on the discriminability of linguistic and non-linguistic stimuli at the cortical level, and b) to examine whether the cortical responses differ based on the chronological age at intervention, the degree of hearing loss, or the acoustic stimulation mode in children with severe and profound hearing loss. Methods: Mismatch negativity (MMN) responses were collected from 43 children with severe and profound bilateral sensorineural hearing loss, and 20 children with normal hearing (age: 3–6 years). In the non-verbal stimulation condition, pure tones with frequencies of 1 kHz and 1.1 kHz were used as the standard and the deviant respectively. In the verbal stimulation condition, the Chinese mandarin tokens/ba2/and/ba4/were used as the standard and the deviant respectively. Latency and amplitude of the MMN responses were collected and analyzed. Results: Overall, children with hearing loss showed longer latencies and lower amplitudes of the MMN responses to both non-verbal and verbal stimulations. The latency of the verbal/ba2/–/ba4/pair was longer than that of the nonverbal 1 kHz–1.1 kHz pair in both groups of children. Conclusions: Children with hearing loss, especially those who received intervention after 2 years of age, showed substantial weakness in the neural responses to lexical tones and pure tones. Thus, the chronological age when the children receive hearing intervention may have an impact on the effectiveness of discriminating between verbal and non-verbal signals.